Empirical and numerical-based predictive analysis of a single-axis PV system under semi-arid climate conditions of Pakistan - Saeed, Farwa; Ghafoor, Abdul; Hussain, Muhammad Imtiaz; Ikram, Kamran; Faheem, Muhammad; Shahzad, Muhammad; Amjad, Waseem; Omar, Muhammad Mubashar; Lee, Gwi Hyun (Frontiers in Energy Research, 2024)
Power generation from fossil fuels is the biggest challenge in the next half of the century.Alternative power generation techniques such as solar photovoltaic (PV) have a potential to act as a future fuel with a challenge to efficiently convert the harvested solar energy into electrical power. This investigation conclusively focused on setting 2.160 kW solar PV system capable of working at higher efficiency by developing a mechanical structure that optimizes power production and minimize energy losses. Besides that, solar PV system efficiencies at various tracking positions, performance coefficient during rainy and sunny days, as well as system degradation rate have also been investigated. Pvsyst v6.8 simulation tool was used for getting the simulated results and were compared with the actual experimental results. The parameters considered for the investigations include ambient temperature, irradiance, solar PV module surface temperature, solar PV voltage and current, wind velocity and atmospheric turbidity.Evaluation of the solar PV system was done based on two modes such as M1 (No tracking/fixed type) and M2 (manual tracking by changing position of the solar PV System every hour). The predictive results obtained from pvsyst v6.8 concluded that total energy production from the installed system was 3242 kWh/yr and 3984 kWh/yr. The performance ratio (PR), obtained from simulation, was 72% and 78% for M1 and M2, respectively, which was consistent with the experimental results i.e., 70% and 72% for M1 and M2 respectively. Similarly, the power conversion efficiency under standard temperature and conditions for both modes, simulated and experimental were found to be 16.50 and 12.75%, respectively. The estimated degradation rate was observed in the range of -0.6 to -5.0%.